Testing of municipal solid waste recycling program using internet application in Hulu Selangor district - Azman, Mohamad Yusairi (2023)
Recycling in Malaysia is not a new concept as they began since 1990s; however, we are still not reaching the set target for recycling rate, even there are so many initiatives and programs introduced by the government. Solid waste generation has increased, and environmental impacts related to improper management of waste has yet to cease. Due to advancement of technology, internet application is currently being integrated into the recycling program to increase participation of public. The objective of this study is to investigation on testing of municipal waste recycling program using internet application in five (5) residential areas in Hulu Selangor. It is found that there are eighteen (18) recyclables generated, and the top recyclables are (31.2%) extras, (14%) clothes, (10.5%) cardboards, and (9.6%) plastic bottles. Most neighbourhoods gather plastic products and paper products more than metal products and electrical and electronics. In comparison, Adenium Residence has the highest tonnage/cap/month with 3.22kg with total tonnage of 2,166.03kg/year, followed by 2.11kg by Seri Bakawali Apartment with total tonnage of 1,420.0kg/year, 1.8kg by Kuala Kubu Bharu with total tonnage of 1,434.9kg/year, 0.58kg by Desa Melor Residence with total tonnage of 469.5kg/year and 0.45kg by Rajawali Residence with total tonnage of 141.9kg/year. As recommendation, the local authority should further expand the program to other residential areas, adopt Act 672 or make their own policy regarding waste segregation, implement circular economy and practice waste prevention and waste minimization.